Depressive symptoms and associated factors among HIV positive patients attending public health facilities of Dessie town: A cross-sectional study - Yitayish Damtie; Bereket Kefale; Melaku Yalew; Mastewal Arefaynie; Bezawit Adane; Afework Edmealem; Atsedemariam Andualem (PLoS ONE, 2021)
Background Depressive symptoms are the most common psychiatric complication of Human Immunodeficiency Virus (HIV) infection. They are associated with poor drug adherence, treatment failure, and increase the risk for suicide. There was limited evidence of depressive symptoms among HIV-positive patients in the study area. So, this study aimed to determine the prevalence of depressive symptoms and associated factors among HIV-positive patients attending public health facilities of Dessie town, North-central Ethiopia, 2019. Method A cross-sectional study was conducted on 380 HIV-positive patients attending ART clinics in Dessie town, North-central Ethiopia, 2019. Samples were selected using systematic random sampling and the data were collected by using structured, pretested, and interviewer-administered questionnaires. Patient Health Questionnaire (PHQ-9) at a cut-off point of 5 was used to assess depressive symptoms. The data were entered by Epi data version 3.1 and analyzed by SPSS version 25. A binary logistic regression model was used to identify factors associated with depressive symptoms. The Adjusted Odds Ratio (AOR) along with a 95% Confidence Interval (CI) was estimated to measure the association. The level of significance was declared at a p-value of less than 0.05. Result The prevalence of depressive symptoms among HIV positive patients was 15.5% (95% CI: (12.4%, 19.2%)). Age 40–49 years compared to 30–39 years (AOR = 2.96, 95% CI: (1.01, 8.68)), age ≥50 years compared to 30–39 years (AOR = 3.81, 95% CI: (1.05, 13.8)), having perceived stigma (AOR = 10.2, 95%CI: (4.26, 24.4)) taking medication other than Antiretroviral Therapy (ART) (AOR = 2.58, 95% CI: (1.25, 5.33)) and history of opportunistic infections (AOR = 5.17, 95% CI: (1.31, 20.4)) were factors associated with depressive symptoms. Conclusion The prevalence of depressive symptoms was low compared to previous studies. Age, perceived stigma, taking medication other than ART, and history of opportunistic infections were factors associated with depressive symptoms. Health education and counseling programs should be strengthened and target older patients, patients who took medications other than ART, patients who experienced perceived stigma and patients with a history of history opportunistic infections.